PELATIHAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA UNTUK UMKM DESA CANGKUANG, KECAMATAN LELES, KABUPATEN GARUT, JAWA BARAT - Apriliana, Tria; Agustina, Ingrid Larasati; Susiani, Rini; Yusuf, Paulus Sugianto; Ilyas, Supriyanto (LPPM Universitas Bina Bangsa, 2025)
Widyatama University, in collaboration with Small and Medium Enterprises (MSMEs) and the Cangkuang Village Office, Leles District, Garut Regency, provided Training on Preparing Simple Financial Reports for the Cangkuang Village MSME Group to gain knowledge and skills so that they can provide direction and assistance to the MSME Group below the supervision of the Village Office. Suggestions and appropriate solutions will help solve the problems of recording transactions and financial reports faced by business people, who generally have low education and lack the understanding and ability to prepare financial reports.